Caves and karst of the Yorkshire dales, Volume 2: The Caves - Šušteršič, France (Acta Carsologica, 2019)
The book is the obvious complement and continuation of the first part, which was published in 20131. One must emphasize that the two volumes are intended to be just the beginning of a series of similar publications that will cover all important karst regions in Britain. As before, the actual, paperback issue (hardback is also available) is in A4- format. In the future both volumes will be accessible as electronic versions, and some of the digital chapters will undergo revision if significant discoveries or scientific breakthroughs are made.